KINERJA GURU PAUD DALAM MENGIMPLEMENTASIKAN STANDAR TINGKAT PENCAPAIAN PERKEMBANGAN ANAK USIA DINI - Revita Yanuarsari; Dianti Yunia Sari; Iim Nurjanah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The background of this research is the number of PAUD institutions that have been established but are not matched by qualified human resources (teachers). Therefore, the purpose of this study was to obtain an overview and information about the performance of PAUD teachers in implementing the standards for the level of achievement of child development. The research method used is descriptive qualitative research method. The study concludes that there is a lack of understanding of teachers regarding aspects of professional and pedagogic competence, an imbalance in the ratio of teachers and children and the use of learning resources is limited to textbooks so that the assessment is only sourced from summative and portfolio tests so that it tends to emphasize the field of basic ability development, and the obstacles faced by teachers. PAUD is mostly due to external factors.